2018
DOI: 10.1002/ange.201711314
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Dynamic Chemical Kinetics at Individual Molecular Ruthenium Catalysts

Abstract: Catalytic cycles are typically depicted as possessing time-invariant steps with fixedr ates.Y et the true behavior of individual catalysts with respect to time is unknown, hidden by the ensemble averaging inherent to bulk measurements. Evidence is presented for variable chemical kinetics at individual catalysts,w ith af ocus on ring-opening metathesis polymerization catalyzedb yt he second-generation Grubbs ruthenium catalyst. Fluorescence microscopyi su sed to probe the chemical kinetics of the reaction becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…The study of catalytic reactions at the single-molecule level has provided a modern perspective for investigating various chemical and biochemical processes with unprecedented spatial and temporal resolution. When the reaction product or any intermediate in the catalytic cycle is a fluorescent species, the localization or tracking of the catalyst over time, using advanced optical fluorescence microscopy methods, allows for the direct measurement of the stochastic fluctuation of the reaction dynamics underlying the process. This approach enables the investigation of catalytic organic and inorganic reactions, enzyme reactions, and other complex processes at the single-molecule (SM), atom, or nanoparticle levels. These methods surpass classical macroscopic kinetics under deterministic conditions because they offer a more specific analysis of the turnover frequency (TOF) of the catalyst using a very small amount of reactants, which is an important consideration in today’s research. The Suzuki–Miyaura cross-coupling reaction is widely applied in organic synthesis, representing one of the most crucial methods for extending the carbon framework in desired large organic compounds .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The study of catalytic reactions at the single-molecule level has provided a modern perspective for investigating various chemical and biochemical processes with unprecedented spatial and temporal resolution. When the reaction product or any intermediate in the catalytic cycle is a fluorescent species, the localization or tracking of the catalyst over time, using advanced optical fluorescence microscopy methods, allows for the direct measurement of the stochastic fluctuation of the reaction dynamics underlying the process. This approach enables the investigation of catalytic organic and inorganic reactions, enzyme reactions, and other complex processes at the single-molecule (SM), atom, or nanoparticle levels. These methods surpass classical macroscopic kinetics under deterministic conditions because they offer a more specific analysis of the turnover frequency (TOF) of the catalyst using a very small amount of reactants, which is an important consideration in today’s research. The Suzuki–Miyaura cross-coupling reaction is widely applied in organic synthesis, representing one of the most crucial methods for extending the carbon framework in desired large organic compounds .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Further expansion of these studies into polymer tethers for catalysts was suggested as a future opportunity for additional studies, and several of these works were performed to fill the gap in polymer initiation via catalysis. 26,[153][154][155][156]…”
Section: Catalytic Synthesismentioning
confidence: 99%
“…219 These studies were eventually expanded to determine individual molecule kinetics of ruthenium catalyst-governed ROMP which varied from bulk concentration kinetics for the same reaction. [154][155][156] At a molecular level, catalysis kinetics vary depending on local environments, and at low concentrations of substrate, single monomer insertion events could be imaged within the precipitated polymer. Therefore, these methods of reaction monitoring have been limited to polymers of substantial molecular weight but not of oligomeric growth toward reaching entanglement molecular weight.…”
Section: Catalyzed Polymerizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include studies of polymer SM diffusion and polymer brush nanoscale properties, conformational changes and reactions of enzymes, and heterogeneous chemical reactions catalyzed at planar surfaces and nanoparticles. In a fluorogenic reaction, where the product is a fluorescent species, SM fluorescence microscopy can provide a direct observation of the turnover rate of the catalytic process on a site-by-site basis, and the detailed information obtained provides insights into the design of new and better catalysts. Indeed, recent SM studies of various organic and inorganic catalytic processes have led to many interesting and important discoveries. While this approach has primarily been employed to study hydrolysis and elimination reactions, this is not a fundamental limitation, and SM methods can potentially leverage fluorogenic reactions to study a much broader range of useful and important chemical processes, including bimolecular bond-making reactions such as condensation as described here.…”
mentioning
confidence: 99%